Kompetensi Supervisor Dalam Supervisi Guru Bimbingan Konseling (Suatu Tinjauan Studi Pustaka) - Ilfana, Aulia; M, H Karlina (Jurnal Paedagogy, 2022)
This study aims to describe the competence of supervisors in the supervision of counseling guidance teachers. This research method uses a literature study which contains the concepts and theories used based on the available literature, especially from articles published in various scientific journals. Furthermore, the data analysis technique used interpretive descriptive analysis. The results of this study indicate that the supervision of guidance and counseling teachers is proven to be effective in increasing the skills, understanding of counseling teachers and able to increase the mastery of counseling practice. Where with the implementation of counseling guidance supervision carried out by supervisors, it can help counseling guidance teachers to improve and further develop skills in counseling guidance service skills. The supervisory role requires many different skills and values from the therapeutic relationship. Supervisors must have the education and training to carry out their role so that counseling teachers receive regular feedback so that they have a basis on which to hone their skills.